Design of an adaptive sliding mode controller for efficiency improvement of the MPPT for PV water pumping. (2019) - Miqoi, Sabah; Ougli, Abdelghani El; Tidhaf, Belkassem
This paper represents a conception and simulation of a photovoltaic (PV) water pump along with a new maximum power point tracker (MPPT) control to ensure the operation of the PV system at a maximum power for various climatic conditions. In particular, we propose a robust tracking controller, an adaptive sliding mode control (ASMC). Our system includes a PV panel, DC/DC boost converter, a DC motor, a centrifuge water pump and an MPPT controller that generates the duty cycle to the boost converter. The proposed controller is compared to a sliding mode control (SMC) and a classic perturb and observe (P&O) algorithm. The system is simulated in MATLAB/Simulink and the results show the good functioning and the improvement of the performance of the PV system using the proposed controller.